2018
DOI: 10.3892/mmr.2018.8898
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of dexmedetomidine on traumatic brain injury: Involvement of neuronal apoptosis and HSP70 expression

Abstract: The aim of the present study was to investigate the protective effect of dexmedetomidine (Dex) on traumatic brain injury (TBI), and further evaluate whether the underlying neuroprotective mechanisms are associated with neurological apoptosis and the expression of 70 kDa heat shock protein (HSP70) in the hippocampus. A total of 90 adult male Sprague-Dawley rats were randomly assigned into 3 groups (n=30/group): Sham, TBI and Dex groups. The rat models of TBI were established using a modified weight-drop device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The Bcl‐2 family consists of antiapoptotic (Bcl‐2) and proapoptotic (Bax) factors. The pro‐apoptotic family members trigger cytokine release into the cytoplasm, leading to caspase activation . In present study, Bax and Bcl‐2 expression levels were detected using Western blotting.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The Bcl‐2 family consists of antiapoptotic (Bcl‐2) and proapoptotic (Bax) factors. The pro‐apoptotic family members trigger cytokine release into the cytoplasm, leading to caspase activation . In present study, Bax and Bcl‐2 expression levels were detected using Western blotting.…”
Section: Discussionmentioning
confidence: 85%
“…Dexmedetomidine (DEX) is a central adrenoceptor α 2‐adrenergic receptor agonist with sedative, analgesic, and anti‐stress reaction effects . DEX affects neurons and exerts protective effects by decreasing catecholamine and glutamate levels and preventing neuronal apoptosis . Previous studies demonstrated that suppressing proinflammatory cytokine production in the brain played a crucial role in DEX–induced neuroprotection after cerebral ischemia/reperfusion injury .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (37) recently reported that HSP70 conferred cellular protection against ischemic insults and possessed potent anti-apoptotic properties in hippocampal neurons using a traumatic brain injury rat model. To further understand the role of apoptosis and autophagy in neurons after I/R, protein expression levels of Bax, Bcl-2, Caspase-3 and Beclin1 were analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that dexmedetomidine can serve as a neuroprotective agent against brain injury via the inhibition of neuronal apoptosis ( 34 ). Sun et al ( 35 ) identified that dexmedetomidine confers neuroprotection against spinal cord ischemia-reperfusion injury via the suppression of spinal cord inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%